People's response to disaster: A population based study of the victims of 2018 flood in Kerala, South India - Pramod Thomas; Sangeetha M Varghese; Anoop I Benjamin (Wolters Kluwer Medknow Publications, 2023)
Background: Natural disasters cause much hardship and suffering, loss of property, and increased morbidity and mortality amongst those affected. Timely and effective response for relief and rescue services go a long way in mitigating these consequences. Material and Methods: This population-based cross-sectional, descriptive study conducted in the immediate aftermath of the catastrophic flood that occurred in Kerala, South India, in 2018, documents the experiences of the victims, the community's preparedness, and response to the disaster. Results: Flood waters reached levels of over four feet within the premises of 55% of the houses and nearly 97% had water flooding inside their homes. More than 93% of the households were evacuated to safer locations and relief camps. The elderly and those with chronic illnesses were the worst sufferers, unable to access medical aid. Many families (62%) received help from neighbors. Conclusion: However, the loss of lives was minimal, and could be attributed to the immediate response of the local community in rescue and relief work. This experience underscores the vital importance of the local community as first responders, and their preparedness for disasters.